Learning Strategies of Gifted Students as a Factor of Success In Foreign Language for Specific Purposes Learning - Aleksandra J. Gojkov Rajić; Јеlisaveta F. Šafranj (University of Belgrade, Teacher Education Faculty, 2022)
Theoretical context of the paper refers to Sternberg's Theory of Mental Self-Government and Deci's Theory of Self-Regulation. The method of systematic non-experimental observation was used. The research aim was to find out which learning strategies are used by gifted students and what their impact is on learning outcomes in order to address the demands imposed upon the students to develop a whole range of foreign language learning strategies facilitating their independence in learning, i.e., allowing them to self-regulate their own language learning. The research is of exploratory character and quantitative approach was applied. Convenience sampling was used and the sample consisted of 200 students from universities in Novi Sad and Belgrade. The students with average mark above 9,70 are considered academically gifted (N=19). The following instruments were used: The test of knowledge of foreign languages for specific purposes designed for the purpose of the research; the Questionnaire GD - General data, the Inventory of strategies for foreign language learning (SILL) - modified version (German, English). The basic findings are as follows: 1) The differences found between the academically gifted and the rest of the students at the scales of different strategies do not suggest statistical significance, but the differences within proactive and experiential strategies are rather close to significant and point to the tendency of the gifted students to use these strategies to a greater extent than the rest of the students. 2) The level of foreign language acquisition correlates with the choice of learning strategies used by the gifted students, but the analysis of the latent groups and the analysis of the variance has confirmed the existence of the statistically significant differences between certain groups, suggesting that the latent profile (high application of proactive and experiential strategies) is associated with significantly higher test results, differentiating these students from others. In other words, the success in foreign language for specific purposes learning is related to the choice of employed learning strategies.